Report of the first prototype of non-imaging focusing heliostat and its application in high temperature solar furnace - Chen, Y. T.; Chong, K. K.; Lim, C. S.; Lim, B. H.; Tan, K. K.; Aliman, Omar; Bligh, T. P.; Tan, B. K.; Ismail, Ghazally (Elsevier, 2002)
Following the publication on the principle and theory of a newly proposed non-imaging focusing heliostat, this paper presents a report on the design, optical alignment and application of the first prototype heliostat. In the architecture of the first prototype, 25 mirrors, each with a dimension of 40×40 cm, are arranged into five rows and five columns to form a total reflective area of 4 m2. The design of the essential part of the first prototype heliostat will be discussed in this paper, which consists of two primary elements; a rotation–elevation system for tracking a mirror support frame which carries 25 mirror facets, and a separate two-axis tracking system for compensating (each second) off-axis aberrations of 24 slave facets relative to the central mirror, which is fixed in the mirror frame. The rotation–elevation system consists of a pedestal supporting a rotational tracking mechanism carrying a U-shaped arm and a second tracking system for tracking a moving frame in elevation. The moving frame carries a central stationary (relative to the frame) mirror, called a master mirror. Slave mirrors are arrayed in five rows and five columns, and eight stepper motors drive the outer four rows and columns relative to the master mirror via a computer programme implementing newly proposed formulas to eliminate the first-order aberration. With a second stage concentrator comprising a small aperture size parabolic mirror (diameter of 60 cm), a cost-effective high temperature solar furnace was constructed. In our experiment, the highest furnace temperature of 3400°C has been recorded through the melting of pure tungsten wires.